Semi-slant Submanifolds of Trans-Sasakian Manifolds - Khan, Viqar Azam; Khan, Meraj Ali (Sarajevo Journal of Mathematics, 2024)
The purpose of the present paper is to study semi-slant submanifolds of a trans-Sasakian manifold. 2000 Mathematics Subject Classification. 53C40, 53B25